Feto-maternal outcome in patients with couvelaire uterus: a 3 year study in a tertiary care hospital in rural Karnataka, India - N., Sunanda; T., Sruthi; S. R., Sheela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Couvelaire uterus also known as uteroplacental apoplexy is a life threatening condition where abruptio placenta causes bleeding that penetrates into the uterine myometrium. It can only be diagnosed on direct visualization. Therefore, its occurrence is perhaps under reported and underestimated in the literature. The objective of this study was to determine the risk factors for couvelaire uterus and feto-maternal outcomes associated with couvelaire uterus in comparison with patients who presented with abruption without couvelaire uterus in a tertiary care hospital in rural Karnataka. Methods: All women who had abruptio placenta who were delivered by cesarean section were included in the study. Cases were women with couvelaire uterus and controls were women without couvelaire uterus observed intraoperatively during cesarean section. Results: Patients without couvelaire uterus had significantly more vaginal bleeding (22.2% vs 75%). However, patients with couvelaire uterus had a higher incidence of PPH (66.7% vs 28.6%), need for blood transfusion (5.9±3.2 pints vs 1.6±1.8 pints), DIC (22.2% vs 14.3%), maternal mortality (5.6% vs 0) and adverse neonatal outcome. Conclusions: We conclude that patients with couvelaire uterus had an increased risk of maternal complications such as postpartum hemorrhage and disseminated intravascular coagulation which resulted in increased need for blood transfusion, prolonged hospital stay and maternal morbidity and mortality. Present study further highlights that adverse neonatal outcomes such as low birth weight, low Apgar score and neonatal death were more frequently associated with couvelaire uterus. Thus, the presence of couvelaire uterus may be considered as a severe form of abruption and such patients should be anticipated for higher incidence and risk for maternal and neonatal morbidity.